Tonoplast-Localized Theanine Transporter CsCAT2 May Mediate Theanine Storage in the Root of Tea Plants (Camellia sinensis L.) - Feng, Lin; Yu, Yongchao; Lin, Shijia; Yang, Tianyuan; Chen, Qi; Liu, Linlin; Sun, Jun; Zheng, Pengcheng; Zhang, Zhaoliang; Wan, Xiaochun (Frontiers in Plant Science, 2021)
Theanine is the component endowing tea infusion with “umami” taste and anti-depression benefits. Theanine is primarily synthesized and stored in root in winter, and is transported via vascular tissues to the new shoot in spring. However, the mechanism underlying theanine storage in the root of tea plants remains largely unknown. CsCAT2 (Cationic amino acid transporter 2) in tea plants is homologous to glutamine permease (GNP1), the specific glutamine transporter in yeast. In this study, we identified CsCAT2 as an H+-dependent theanine transporter with medium affinity for theanine. The result of subcellular localization showed that CsCAT2 was a tonoplast-localized transporter. Importantly, CsCAT2 highly expressed in the root in winter during theanine storage, and reduced its expression in the root during theanine transport from root-to-shoot in spring. In addition, CsCAT2 expression in the roots of 5 varieties at four time points during December and April was significant negatively correlated with the capacity of theanine root-to-shoot movement. Taken together, these results suggested that CsCAT2 may mediate theanine storage in the vacuole of root cells and may negatively modulate theanine transport from root to shoot.